In vitro tests to assess the effectiveness of tamarind (Tamarindus indicus) and oxalic acid solutions against cattle tick, Rhipicephalus (Boophilus) microplus - Álvarez C, Víctor (2015)
An in vitro assay was performed to measure the acaricidal effectiveness of crude-extract of tamarind (Tamarindus indicus) to control the engorged female cattle tick (Rhipicephalus microplus). In addition, a product formulated with oxalic acid (OA) was tested. Parameters measured were percentage of oviposition inhibition and control rate. The best result was obtained with oxalic acid to twice the concentration recommended by the manufacturer for varroa control, followed by the tamarind pulp at 1:3 and 1:4 concentrations. Even though other concentrations of ferment of tamarind crude-extract and half dose of the oxalic acid recommended had lower values, all cases were above 60%, showing a detrimental effect on the tick population. Observations were made of treated ticks using a stereoscope 1-3 hours after the treatment and major injuries were detected. These results support the hypothesis that OA and the crude-extract of tamarind fruits could potentially help to control R. microplus, especially as part of an integral control program against ticks.